Novel cytomegalovirus variants in immunocompromised hosts: genetic insights and clinical significance - Alsweed, Abdulrahman M.; Alsanea, Madian S.; Almaghrabi, Reem S.; Al-Qahtani, Ahmed A.; AlSuhaibani, Mohammad; Alhajjar, Sami H.; Alhamlan, Fatimah S. (Frontiers in Microbiology, 2025)
BackgroundHuman cytomegalovirus (HCMV) is a significant opportunistic pathogen affecting immunocompromised individuals, particularly solid organ and hematopoietic stem cell transplant recipients. The emergence of mutations within conserved genomic regions of HCMV genes targeted by antiviral therapies, significantly complicating the interpretation of resistance and treatment decisions. Although the molecular characterization of such mutations and their clinical correlation are critical to guide appropriate therapeutic strategies, the significance of many detected mutations and variants, even those in conserved regions, remain uncertain in terms of in vitro or in vivo drug resistance. In this study, we clinically evaluated 15 such novel mutations.MethodsClinical specimens from immunocompromised and transplant patients with confirmed HCMV DNAemia were sequenced for UL97, UL54, and UL56. The detected variants were aligned with the HCMV Merlin reference genome and evaluated for novelty and conservation. Patient records were retrospectively reviewed to assess antiviral regimens, virological responses, and clinical outcomes.ResultsIn total, 13 patients (25%) exhibited novel UL97, UL54, and UL56 mutations. Four patients (30.77%) met the criteria for refractory HCMV DNAemia with varying clinical responses. Some patients responded to first-line antiviral agents despite carrying resistance-associated variants. Notably, the G579C mutation in UL97 and A835T mutation in UL54 were found within conserved domains crucial for kinase and polymerase functions, indicating their potential functional significance. One patient carried the established UL54 P522S mutation, which has been associated with intermediate ganciclovir resistance. Two cases of severe immunosuppression and persistent viremia led to mortality, demonstrating the impact of host immunity on treatment response.ConclusionInterpreting cytomegalovirus (HCMV) drug resistance mutations requires a comprehensive approach that integrates molecular data with clinical context. Early genotypic analysis can guide antiviral therapy; however, improved classification of mutations based on predicted resistance potential and phenotypic characteristics may optimize clinical decision-making. These insights emphasize the need for personalized management strategies in immunocompromised patients.